Potential of using chia seed gel extracted from chia seed as stabiliser in ice cream : a thesis presented in partial fulfilment of the requirements for the degree of Master in Food Technology, Massey University, Auckland, New Zealand - Yu, Yuting (Massey University, 2024)
In the manufacture of ice cream, stabilisers are used as food additives to stabilise the structure of ice cream. Typically, commercial stabilisers used in ice cream include guar gum (GG), locust bean gum (LBG), carrageenan and carboxymethyl cellulose (CMC) which are usually designated with E-numbers on the nutrition panel of food packages. However, most of the consumers have little knowledge about the information on E-numbers and some consumers are sceptical of their presence as food additives in the frozen desserts. Current trends also show that consumers prefer functional food products with natural food ingredients that support better health and wellbeing. Thus, the present study investigated the potential of chia seed gel to replace commercial stabilisers in ice cream. Chia seed is a common household food ingredient, and the gel extracted from hydrated chia seed has strong water absorbing and swelling properties, which gives it the potential of being incorporated into ice cream formulation to replace commercial stabilisers. The study comprised two main phases: extraction of chia seed gel and testing its performance in ice cream as a stabiliser using varying concentrations. In phase I, chia seed gel was extracted at three soaking temperatures (20 ℃, 40 ℃ and 80 ℃) using three seed: water ratios (1:10, 1:20, 1:30, w/w). The yield and apparent viscosity of extracted chia seed gel were determined by Linear Regression Analysis. The optimum extraction of chia seed gel was obtained using soaking temperature at 80 ℃ with a seed: water ratio of 1:10 (w/w), producing 9.943±0.75% (w/w) of dried chia seed gel with an apparent viscosity of 6.74±0.24 Pa·s. In phase II, samples of chia seed gel extracted under the optimised conditions obtained in phase I were incorporated into ice cream formulations (CS₁, CS₂ and CS₃) at three varying concentrations (16.35%, 27.25%, 37.8%, w/w). Two control ice cream samples with/without commercial stabilisers (0.2% guar gum, 0.15% carrageenan, w/w) were also prepared (C₂ and C₁, respectively), giving a total of five ice cream samples. The frozen dessert samples were evaluated for the viscosity of the ice cream mix, overrun, fat globule size distribution, meltdown rate and hardness of ice cream. The ice cream samples were also evaluated by a focus sensory group consisting of five panellists from students at the School of Food and Advanced Technology, Massey University. The most promising ice cream was selected for further consumer sensory evaluation (using a 9-point hedonic scale). The sweetness, creaminess, melting, mouth feel, smoothness, firmness and overall acceptance of the selected ice cream samples were evaluated. The addition of chia seed gel in ice cream increased the viscosity of ice cream mix, overrun, hardness, melting resistance and fat globule size of ice cream. Ice cream containing 27.25% chia seed gel (w/w) received the highest overall consumer sensory scores. The ice cream sample had an overrun of 41.02±0.89% which was slightly lower than the control sample (50.70±0.42%) that contained commercial stabilisers. The experimental frozen dessert was characterised by a hardness of 84.63±6.14 N and fat globule size distribution of 94.46±2.69 µm. The meltdown rate (0.44±0.01 g/min) was low compared to the control ice cream with commercial stabilisers.
Possibly copyrighted Figures remain for the sake of clarity; copyright holders may request their removal using the "Copyright Take Down Request" button below.
Keywords: 300607 Food technology